Referral pattern of patients coming to Mandya Institute of Medical Sciences, Mandya - Vinay, M.; Bharath, J.; Harish, B. R. (International Journal Of Community Medicine And Public Health, 2019)
Background: In the act of medical practice, referral is the transfer of a patient’s care from one physician or clinician to another. Appropriate referral is an integral part of a complete quality health care management. At present, patients can visit any level of health care irrespective of severity of their health condition and most of the burden of these patients is on tertiary centers. This study was done to describe the Referral Pattern of Patients Coming to Mandya Institute of Medical Sciences, Mandya. Methods: It was a cross sectional study conducted from October 2017 to November 2017 with sample size of 400, p=50%. Sampling technique used was convenient sampling and data was collected by interview using the semistructured questionnaire. Results: Among the study population 197 (49.3%) were males and 203 (50.7%) were females, 392 (82.3%) had BPL card. Mean distance travelled by them to MIMS was 17.7±14.8 km. Medicine department n=80 (20%) followed by ophthalmology department n=64 (16%) were the most frequently visited departments. Mean distance to the nearest health center from their place of residence was 3.2%±2.9 km. 148 (37.0%) visited the health center near their place of residence before coming to MIMS and 253 (63.0%) did not visit. Conclusions: Most of the patients visited tertiary healthcare center (MIMS) without visiting health center near to them, though the distance is more and availability of specialists and low cost of treatment were the main reasons for visiting MIMS.